Equilibrium Solubility of Ammonium Nitrate and Potassium Nitrate in (NH4NO3-KNO3-H2O-C2H5OH) Mixed System - Xian Wu; Ganbing Yao; Hao Feng (Crystals, 2025)
The polymorphism of ammonium nitrate has significantly limited its application. Incorporating potassium nitrate into crystals of ammonium nitrate is one of the most commonly used methods to inhibit its polymorphic transition. To accurately prepare crystals of ammonium nitrate with varying contents of potassium nitrate, the solid–liquid phase equilibrium relationship of the quaternary system (NH4NO3-KNO3-H2O-C2H5OH) was studied at 298.15 and 303.15 K. The solubility of components in the equilibrium liquid phase and the composition of the wet-solid phase were determined through formaldehyde titration and gravimetric methods. Based on the solubility data, the phase diagram of the multicomponent system was subsequently constructed. Experimental data demonstrate that the concentration of ammonium nitrate in solution decreases as the potassium nitrate concentration increases. Furthermore, as the ethanol content in the solvent system increases, the equilibrium solubility of ammonium nitrate and potassium nitrate exhibits a concomitant reduction. Correlation analysis of the solubility data for the multicomponent system was performed using the nonrandom two-liquid model. Error analysis demonstrates that the calculated values exhibit satisfactory agreement with the experimental data.